Isotope analysis method (δ¹³C) in clarified apple juice - Figueira, Ricardo [UNESP]; Ducatti, Carlos [UNESP]; Mischan, Martha Maria [UNESP]; Venturini Filho, Waldemar Gastoni [UNESP] (Universidade Federal do Paraná, 2014)
The aims of this study were to develop the method of isotope analysis to quantify the carbon of the C3 photosynthetic cycle in commercial clarifi ed apple juices and to measure the legal limit based on Brazilian legislation in order to identify the beverages that do not conform to the guidelines of the Ministry of Agriculture, Livestock and Food Supply (MAPA). This beverage was produced in a laboratory, according to Brazilian legislation. Adulterated juices with a sugarcane quantity above the legal limit were also produced. Isotope analyses measured the relative isotope enrichment of clarifi ed apple juices and their purifi ed sugar fraction. From these results the C3 source concentration was estimated by means of the isotope dilution equation. To determine the existence of adulteration in commercial juices it was necessary to create a legal limit according to Brazilian legislation. Two commercial brands of clarifi ed juice were analyzed. Taking the C3 source concentration and the ºBrix of commercial clarifi ed juices, together with the legal limit, it was possible to verify that one sample certainly contained more sugarcane than the quantity established by the MAPA. The development of a legal limit was an important methodological innovation that made it possible to identify the beverages that did not conform to Brazilian legislation. The methodology developed proved effi cient for quantifying the carbon of C3 origin in commercial clarifi ed apple juices.

Os objetivos deste trabalho foram desenvolver método de análise isotópica para quantifi car o carbono do ciclo fotossintético C3 em sucos clarifi cados de maçã comerciais e mensurar o limite de legalidade, baseado na legislação brasileira, para identifi car as bebidas que não estão em conformidade com o Ministério da Agricultura, Pecuária e Abastecimento (MAPA). Produziu-se a bebida em laboratório conforme a legislação brasileira. Também foram produzidos sucos adulterados com quantidade de açúcar de cana acima do permitido. Nas análises isotópicas mensurou-se o enriquecimento isotópico relativo dos sucos clarifi cados de maçã e de sua fração açúcar purifi cado. Com esses resultados estimou-se a quantidade de fonte C3 por meio da equação da diluição isotópica. Para determinar a existência de adulteração nos sucos comerciais foi necessária a criação do limite de legalidade de acordo com a legislação brasileira. Duas marcas de suco clarifi cado de maçã foram analisadas. Relacionando a concentração de fonte C3 e o °Brix dos sucos clarifi cados comerciais, juntamente com o limite de legalidade, foi possível verifi car que uma amostra certamente contém mais açúcar que a quantidade estabelecida pelo MAPA. O limite de legalidade constituiu importante inovação metodológica que possibilitou identifi car as bebidas que estavam em inconformidade com a legislação brasileira. A metodologia desenvolvida provou ser efi ciente para quantifi car o carbono de origem C3 em sucos clarifi cados comerciais de maçã.
Método de análise isotópica (δ¹³c) em suco clarificado de maçã
Keywords: Adulteration; Carbon-13; IRMS; Malus domestica; Sugarcane; Adulteração; Carbono-13; IRMS; Malus domestica; Açúcar de cana